Synchronized audio-visual transients drive efficient visual search for motion-in-depth. - Marina Zannoli; John Cass; Pascal Mamassian; David Alais (PLoS ONE, 2012)
In natural audio-visual environments, a change in depth is usually correlated with a change in loudness. In the present study, we investigated whether correlating changes in disparity and loudness would provide a functional advantage in binding disparity and sound amplitude in a visual search paradigm. To test this hypothesis, we used a method similar to that used by van der Burg et al. to show that non-spatial transient (square-wave) modulations of loudness can drastically improve spatial visual search for a correlated luminance modulation. We used dynamic random-dot stereogram displays to produce pure disparity modulations. Target and distractors were small disparity-defined squares (either 6 or 10 in total). Each square moved back and forth in depth in front of the background plane at different phases. The target's depth modulation was synchronized with an amplitude-modulated auditory tone. Visual and auditory modulations were always congruent (both sine-wave or square-wave). In a speeded search task, five observers were asked to identify the target as quickly as possible. Results show a significant improvement in visual search times in the square-wave condition compared to the sine condition, suggesting that transient auditory information can efficiently drive visual search in the disparity domain. In a second experiment, participants performed the same task in the absence of sound and showed a clear set-size effect in both modulation conditions. In a third experiment, we correlated the sound with a distractor instead of the target. This produced longer search times, indicating that the correlation is not easily ignored.